The myth of rescue : why the democracies could not have saved more Jews from the Nazis - Rubinstein, W. D. 1946- (London ; New York : Routledge, 1997)
It has long been claimed that the Allies did little or nothing to rescue Europe's Jews. Did they deny refuge to those fleeing Hitler's death machine? Why did they fail to bomb Auschwitz and the other concentration camps? Could they have actually negotiated with the Nazis for Jewish lives?
Arguing that the rescue of the Jewish people has been consistently misinterpreted, The Myth of Rescue states that no Jew who perished in the Holocaust could have been saved by any action of the Western Allies.
Presenting what was actually known of the Holocaust at the time and what actions were realistically possible, William D. Rubinstein traces the development of the arguments surrounding the debate and debunks the "myths" that were generated in the 1970s and '80s: the myth of the closed-door immigration policies in the years 1933-40 and the plans for rescue proposed by the democracies--including the bombing of concentration camps, the possibility that the War Refugee Board could have saved more Jews, and the rumors of negotiations between the democracies and Nazis to save Jewish lives.
The topic is explored with a historian's skill and presented with the conviction of one who once believed that the democracies did nothing and more Jews could have been rescued but who now, through his own research, has uncovered evidence that the opposite is true.
Includes bibliographical references and index.
The Roger Griffin ComFas Collection
Keywords: World War, 1939-1945 -- Jews -- Rescue; Jews -- Germany -- History -- 1933-1945.; Holocaust, Jewish (1939-1945) -- Causes